2016
DOI: 10.1257/app.20140362
|View full text |Cite
|
Sign up to set email alerts
|

Internal Labor Migration as a Shock Coping Strategy: Evidence from a Typhoon

Abstract: We analyze how internal labor migration facilitates shock coping in rural economies. Employing high precision satellite data, we identify objective variations in the inundations generated by a catastrophic typhoon in Vietnam and match them with household panel data before and after the shock.We find that, following a massive drop in income, households cope mainly through labor migration to urban areas. Households with settled migrants ex-ante receive more remittances. Non-migrant households react by sending ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 45 publications
8
96
2
1
Order By: Relevance
“…Besides the empirical studies noted above, there have also been important theoretical advances. Gröger and Zylberberg (2016) analyze coping mechanisms through labor in-migration of rural economies after catastrophic natural disaster. Specifically, they focus on the impact of typhoon Ketsana in Vietnam during 2009.…”
Section: Literaturementioning
confidence: 99%
“…Besides the empirical studies noted above, there have also been important theoretical advances. Gröger and Zylberberg (2016) analyze coping mechanisms through labor in-migration of rural economies after catastrophic natural disaster. Specifically, they focus on the impact of typhoon Ketsana in Vietnam during 2009.…”
Section: Literaturementioning
confidence: 99%
“…2 The body of evidence on the ability of dispersed social networks to help insure against collective shocks is, however, nuanced. Gröger and Zylberberg (2016) distinguish the insurance effect against correlated shocks based on how widely dispersed household-migrant ties are, and find that while having a migrant household member outside of the origin household's district helps smooth household income in the face of a typhoon, migrant ties to individuals in the same district do not mitigate the effects of this weather shock. Also differentiated, albeit reversed, results emerge in another context: airtime transfers that people made using mobile phones to earthquake survivors in their social network (Blumenstock, Eagle, & Fafchamps, 2016).…”
Section: Social Network Shocks and The Dynamics Of Asset Pathsmentioning
confidence: 99%
“…The empirical literature on the impact of shocks on assets, income, and welfare has used a diverse array of measures of shocks, usually directly informed by the specificities of the empirical context in the studies. Collective shocks, for example, have been captured as a dummy variable for the time and location affected by an earthquake (e.g., Blumenstock et al, 2016), the amount of rainfall by village and year (e.g., Dercon & Christiaensen, 2011), the percentage of an area inundated by water following a typhoon (e.g., Gröger & Zylberberg, 2016), and simply by interacted time-village dummy variables (Jalan & Ravallion, 1999).…”
Section: Shocksmentioning
confidence: 99%
“…Especially since credit constraint restricts relatively deprived or poorer households and individuals from moving from agriculture to modern sector (Banerjee and Newman 1998), and temporary migrants are more likely to remit more (Dustmann and Mestres 2010), internal temporary migration is a common coping strategy in many developing countries (Gröger and Zylberberg 2016). Gröger and Zylberberg (2016) found that Vietnamese households with settled migrants ex ante receive more remittances; whereas non-migrant households send family members away to diversify the sources of income.…”
Section: Figurementioning
confidence: 99%
“…Especially since credit constraint restricts relatively deprived or poorer households and individuals from moving from agriculture to modern sector (Banerjee and Newman 1998), and temporary migrants are more likely to remit more (Dustmann and Mestres 2010), internal temporary migration is a common coping strategy in many developing countries (Gröger and Zylberberg 2016). Gröger and Zylberberg (2016) found that Vietnamese households with settled migrants ex ante receive more remittances; whereas non-migrant households send family members away to diversify the sources of income. 11 We have accounted for the number of dependent children attending school, the number of nonworking dependents (e.g., smaller children and elderly relatives), as well as the number of adult, working-age children living either at home (i.e., live-in) or away from home (i.e., live-away), which allows for the possibility that not all working-age family members contribute to the household labor endowment.…”
Section: Figurementioning
confidence: 99%